55.8k views
2 votes
Solve each of the following equations using a method other than the quadratic formula. y2-6y=0

User Ashford
by
5.5k points

1 Answer

5 votes

Answer:

y = 0 and y = -1/3

Explanation:

y2-6y = 0

You can rewrite it as 2y -6y=0 for easier look,

Take the common factor here is 2y out, we will get:

2y*(1-3y) = 0

We learn that a*b=0 when a=0 or/and b=0 so in this case,

2y*(1-3y) = 0

2 options:

2y = 0

y = 0

and

1-3y = 0

-3y = 1

y = -1/3

Hope this help you :3

User Robb
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.